Ocular manifestations in patients with systemic sclerosis - Kozikowska, Małgorzata (Reumatologia, 2020)
Systemic sclerosis (SSc) is a rare, chronic autoimmune disease with unknown etiology. Its prominent features are fibrosis, vasculopathy and impaired immune response. Disease can also affect eyes leading to various findings in ophthalmological examination. The objective of this study was to determine the prevalence and type of ocular involvement in patients with SSc. A systematic literature review was conducted using electronic databases. A combination of following keywords was used: “systemic sclerosis” and ophthalmology-related search terms, including the keywords “eye”, “ocular” and “ophthalmic”. In conclusion, eyelid and conjunctival abnormalities and dry eye disease are among the most common ocular manifestations of SSc. Their diversity is connected to complexity of the disease.